EFEKTIVITAS KONSELING INDIVIDUAL DENGAN TEKNIK SELF-MANAGEMENT TERHADAP KEDISIPLINAN SANTRI DALAM MENGHAPAL KITAB AL-‘AWAMIL - Ira Rajiatun Hasanah; Ahmad Fadhil; Eni Nuraeni (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This study aims to determine the effectiveness of individual counseling services with self-management techniques in improving the discipline of students in memorizing the Al-'Awamil book at the Miftahussholawat Islamic Boarding School. The study used a pre-experimental design with the One Group Pretest-Posttest Design method. The sample was taken by purposive sampling from 30 female students, focusing on 3 students with the lowest discipline scores based on the pretest results. The instrument used was a discipline questionnaire with indicators of self-control, habituation of good deeds, self-evaluation (muhasabah), and istiqamah, which had been validated and were reliable. After receiving four sessions of individual counseling services, the posttest results showed an increase in the discipline scores of the three students from the low to high category with an average increase of 51.94%. Statistical analysis using the Wilcoxon Signed Rank Test showed that the increase was not statistically significant at the 5% level. However, descriptively, self-management technique counseling services have proven effective in increasing the discipline of students, which is also accompanied by positive behavioral changes in accordance with the values of Imam Al-Ghazali's moral education. This study recommends the implementation of self-management technique counseling services as a supporting strategy for discipline education in Islamic boarding schools.